2003
DOI: 10.1891/jcop.17.1.67.58271
|View full text |Cite
|
Sign up to set email alerts
|

Command Hallucinations: Cognitive Theory, Therapy, and Research

Abstract: Command hallucinations (CH) are a distressing and high-risk group of symptoms that have long been recognized but little understood, with few effective treatments. Research shows that cognitive behavior therapy (CBT) is a promising treatment for hallucinations in general and therefore has a potential role in the treatment of CH. We propose that the development of an effective CBT for CH would be enhanced by a theory specific to this uniquely problematic symptom. In this article we describe and apply such a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…The insults of voice may mirror social shame practices and are focused on specific themes, especially sexuality/sexual attractiveness. Insofar as these voices are experienced as demeaning, devaluing and indicating limitations on aspiration, they fit with the dynamics of social rank theory (Gilbert, 1992) and recommend themselves for specific focus in psychotherapy (Byrne, Trower, Birchwood, Meaden, & Nelson, 2003; Trower, Birchwood, Bryne, & Meaden, 2004).…”
Section: Discussionmentioning
confidence: 76%
“…The insults of voice may mirror social shame practices and are focused on specific themes, especially sexuality/sexual attractiveness. Insofar as these voices are experienced as demeaning, devaluing and indicating limitations on aspiration, they fit with the dynamics of social rank theory (Gilbert, 1992) and recommend themselves for specific focus in psychotherapy (Byrne, Trower, Birchwood, Meaden, & Nelson, 2003; Trower, Birchwood, Bryne, & Meaden, 2004).…”
Section: Discussionmentioning
confidence: 76%
“…Auditory hallucinations are amongst the most treatment resistant schizophrenic symptoms. Command hallucinations are the auditory hallucinations that imply the greatest risk for the patient and his/her environment, being the most treatment-resistant and frequent (53% of all voices) (Byrne et al, 2003; Shawyer et al, 2003). The auditory cognitive model (Birchwood et al, 2004; Van der Gaag et al, 2003) has demonstrated that patients perceive voices as damaging and humiliating if commands are not carried out.…”
Section: Outcomementioning
confidence: 99%
“…Acceptance is presented as an alternative way of relating to voices, with emphasis placed on learning to live with the voices rather than attempting to resist them. Cognitive therapy for 'command hallucinations' (CTCH) is an example of the latter approach as it draws upon Social Rank Theory to understand the dominance hierarchies that maintain appraisals of voice (as having absolute power) and self (as subordinated) (Byrne, Trower, Birchwood, Meaden, & Nelson, 2003). The use of cognitive therapy techniques to target and modify this power relationship has resulted in reductions in the perceived power of the voice and a reduced risk of compliance behaviour (Byrne, Birchwood, Trower, & Meaden, 2006;Trower et al, 2004).…”
Section: Discussionmentioning
confidence: 99%